Electromagnetic waves for thermonuclear fusion research - Mazzucato, E. (Ernesto) (World Scientific, 2014)
The science of magnetically confined plasmas covers the entire spectrum of physics from classical and relativistic electrodynamics to quantum mechanics. During the last sixty years of research, our initial primitive understanding of plasma physics has made impressive progress thanks to a variety of experiments - from tabletop devices with plasma temperatures of a few thousands of degrees and confinement times of less than 100 microseconds, to large tokamaks with plasma temperatures of up to five hundred million degrees and confinement times approaching one second. We discovered that plasma con.